A physiologically based pharmacokinetic model of voriconazole integrating time-dependent inhibition of CYP3A4, genetic polymorphisms of CYP2C19 and predictions of drug-drug interactions - Li, Xia; Frechen, Sebastian; Moj, Daniel; Lehr, Thorsten; Taubert, Max; Hsin, Chih-hsuan; Mikus, Gerd; Neuvonen, Pertti J.; Olkkola, Klaus T.; Saari, Teijo I.; Fuhr, Uwe (Clinical pharmacokinetics, 2020)
Voriconazole, a first-line antifungal drug, exhibits nonlinear pharmacokinetics (PK), together with large interindividual variability but a narrow therapeutic range, and markedly inhibits cytochrome P450 (CYP) 3A4 in vivo. This causes difficulties in selecting appropriate dosing regimens of voriconazole and coadministered CYP3A4 substrates.